2013
DOI: 10.2147/ijn.s50991
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous silica nanoparticles synthesized from liquid crystal display manufacturing extracts as a potential candidate for a drug delivery carrier: evaluation of their safety and biocompatibility

Abstract: Mesoporous silica nanoparticles (MSNs) were synthesized as a promising drug delivery carrier due to the large surface area and porous characteristics. Our previous study successfully recycled wastes from the liquid crystal display (LCD) industry as the silica precursor. In this study, we substantiated the possibility of applying this material as a drug carrier. MSNs synthesized from the extraction of wastes from the manufacture of LCD panels were characterized as having an average diameter of 100 nm, a surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Figure h exhibited the BJH adsorption average pore diameter (4 V/A): 38.857 Å (∼3.86 nm) with a peak ∼30 Å (∼3 nm), and the mesostructure of MSNs were very uniform with the BET surface area of 780.6159 m 2 g –1 and a pore volume at P / P o = 0.97 of 0.72 cm 3 g –1 . Various research groups engaged in synthesis of MSNs have also observed similar type IV isotherm patterns and trends related to surface area, pore volume, and average diameter. , …”
Section: Resultsmentioning
confidence: 83%
“…Figure h exhibited the BJH adsorption average pore diameter (4 V/A): 38.857 Å (∼3.86 nm) with a peak ∼30 Å (∼3 nm), and the mesostructure of MSNs were very uniform with the BET surface area of 780.6159 m 2 g –1 and a pore volume at P / P o = 0.97 of 0.72 cm 3 g –1 . Various research groups engaged in synthesis of MSNs have also observed similar type IV isotherm patterns and trends related to surface area, pore volume, and average diameter. , …”
Section: Resultsmentioning
confidence: 83%